PoPoolation: a toolbox for population genetic analysis of next generation sequencing data from pooled individuals. - Robert Kofler; Pablo Orozco-terWengel; Nicola De Maio; Ram Vinay Pandey; Viola Nolte; Andreas Futschik; Carolin Kosiol; Christian Schlötterer (PLoS ONE)
Recent statistical analyses suggest that sequencing of pooled samples provides a cost effective approach to determine genome-wide population genetic parameters. Here we introduce PoPoolation, a toolbox specifically designed for the population genetic analysis of sequence data from pooled individuals. PoPoolation calculates estimates of θ(Watterson), θ(π), and Tajima's D that account for the bias introduced by pooling and sequencing errors, as well as divergence between species. Results of genome-wide analyses can be graphically displayed in a sliding window plot. PoPoolation is written in Perl and R and it builds on commonly used data formats. Its source code can be downloaded from http://code.google.com/p/popoolation/. Furthermore, we evaluate the influence of mapping algorithms, sequencing errors, and read coverage on the accuracy of population genetic parameter estimates from pooled data.